Risks and Uncertainties of Scientific Innovations in French Liability Law: Between Radical Departure and Continuity - Vergès, Etienne (McGill Law Journal / Revue de droit de McGill, 2014)
The author investigates changes in French liability law that have occurred since the end of the nineteenth century as a result of innovation in science and technology and, in particular, of the risks and uncertainties attached to this phenomenon. This text explores the extent to which scientific and technological innovation has influenced legal innovation in the field of civil liability. The author seeks to address whether science- and technology-based legal developments resulted in radical departures from the general principles of civil liability, or rather take place within a continued evolution of the law. This study demonstrates that the impact of scientific and technological innovation on liability is ambivalent; changes in the French law of civil liability have constituted both a radical departure and a continuity of orthodox practice.